Apolipoprotein E polymorphism, life stress and self-reported health among older adults. Issue 4 (13th March 2008) - Zhang, F; Lewis, M; Yang, G; Iriondo-Perez, J; Zeng, Y; Liu, J
Abstract : Objective: To examine the association of self-reported health (SRH) with the apolipoprotein E (APOE) gene, life stress, and sociobehavioural factors in adults aged 55 and over. Design: Secondary analysis of data from the Social Environment and Biomarkers of Aging Study (SEBAS) in Taiwan in 2000, comprising 1023 individuals in 24 communities, using multilevel logistic regression. Results: Allele frequencies are 7.9%, 84.7% and 7.4% for E2, E3 and E4, respectively, similar to those reported in other populations of Asian origins. The apolipoprotein E4 (APOE4) allele was significantly associated with poor SRH overall (odds ratio (OR) 1.54, 95% confidence interval (CI) 1.03 to 2.35), but the association was stronger in women (OR 2.13, 95% CI 1.17 to 3.88) than in men. Individuals who were not satisfied with their living arrangement (OR 3.24, 95% CI 1.99 to 5.29), lived with more than five people in a household (OR 1.52, 95% CI 1.11 to 2.09) or suffered from housing damage in the 1999 earthquake (OR 1.54, 95% CI 0.99 to 2.39) were more likely to report negatively on their heath. Individuals who had secondary education (OR 0.52, 95% CI 0.30 to 0.91), often ate vegetables and fruits (OR 0.69, 95% CI 0.5 to 0.94) or exercised often (OR 0.54, 95% CI 0.38 to 0.77) were less likely to negatively rate their health. A significant interaction between the APOE4 allele and physical exercise was found to be associated with SRH. Conclusions: The APOE4 allele and life-stress factors are associated with SRH, especially in women. Physical exercise is good for health, but benefits may be attenuated among APOE4 allele carriers. This is the first evidence associating a genetic factor and an interaction between APOE4 and physical exercise with SRH. We suggest that well studied genetic factors should be included in health research to control potential heterogeneity.